The Urgency of the International Criminal Court’s (ICC) Jurisdiction in Handling Serious Violations of Human Rights Case of the Uyghur - Aulya, Layla Putri; Arifin, Ridwan; Smith, Robert Brian (The Digest: Journal of Jurisprudence and Legisprudence, 2023)
The international community is currently confronted with a severe humanitarian crisis involving the Uyghur population in Xinjiang, China, marked by pervasive reports of egregious human rights violations, encompassing forced labor, forced assimilation, and mass detention. This study accentuates the imperative for the International Criminal Court (ICC) to assert its jurisdiction and launch an investigation into the alleged crimes against humanity perpetrated against the Uyghur people. The Uyghur case presents a distinctive challenge for the ICC, given the complex political dynamics surrounding China's global influence and its non-membership in the Rome Statute. Nevertheless, this study contends that the ICC's role in addressing such severe human rights violations is now more crucial than ever. It delves into the legal avenues for ICC jurisdiction, exploring potential grounds under the principle of universality and the possibility that some alleged crimes may qualify as war crimes or crimes against humanity. Furthermore, the study delves into the ethical imperative compelling the international community to take decisive action against systemic abuses, asserting that justice and accountability stand as foundational tenets of international law. It also addresses foreseeable obstacles and objections to ICC jurisdiction, including challenges related to state sovereignty, geopolitical considerations, and the practicalities of prosecuting high-ranking officials. In conclusion, this study underscores the urgency of the ICC asserting jurisdiction in the Uyghur case, presenting an opportunity for the international community to showcase its dedication to upholding human rights and justice in the face of severe violations. The ICC's involvement in addressing these atrocities can serve as a beacon of hope for the victims and a deterrent against future perpetrators of similar crimes.